The first-order structural transition in NiO at high pressure - Alexander G. Gavriliuk; Viktor V. Struzhkin; Anna G. Ivanova; Vitali B. Prakapenka; Anna A. Mironovich; Sergey N. Aksenov; Ivan A. Troyan; Wolfgang Morgenroth (Communications Physics, 2023)
The physics of NiO under applied pressure has long been debated and the material has been a key contributor to our understanding of Mott insulators and strongly correlated materials more generally. Here, the authors perform high-pressure X-ray diffraction measurements reporting a pressure-induced structural phase transition for NiO, which they suggest is linked with the metal-insulator transition of this system.